Experts on super innovators: understanding staff adoption of learning management systems. Issue 1 (2nd January 2018) - Sinclair, Jane; Aho, Anne-Maria
ABSTRACT: Learning management systems (LMSs) are widely used in higher education and offer a gateway to innovative, technology-enhanced teaching and learning. However, many university staff still choose not to adopt them or do not explore the more creative functionality. Previous research has developed models of technology adoption which map observed behaviour but provide limited insight into the development of pedagogy and the conceptual issues affecting adoption. This paper reports findings from a research study which gathered rich, qualitative data from LMS administrators to investigate the development of LMS usage and explore, from their perspective, the attitudes of the many teaching staff they support. These experts are well placed to observe actual LMS use across hundreds of courses and to report the beliefs and concerns expressed by the many teaching staff they support. In-depth interviews were conducted in two institutions and the transcripts were coded using thematic analysis. Our results partly support previous research indicating lack of development in LMS use and pedagogy by most teaching staff, and confirm that barriers such as fear of the technology and apprehension concerning negative effects of adoption are still widespread. However, unlike previous findings, the minority of teachers developing innovative pedagogy (the 'super innovators') did not conform to an age stereotype but were distinguished by personal characteristics. We identify a commonly occurring (although not represented in current models) state of inertia in LMS adoption and explore underlying causes linking not just to technology, but to disruption of pedagogy and, ultimately, to conceptions of teaching. It is important to understand these issues in order to meet the concerns of teaching staff and tackle conceptual barriers which conventional LMS training fails to address.